VD_FINDINFO HC / 2019 / 843 vom 2. Oktober 2019 - VD Tribunal cantonal (2019)
DIVORCE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, ÂGE, FORMATION PROFESSIONNELLE, ASSURANCE-VIE | 125 CC, 317 al. 1 CPC (CH)